Intestinal microflora and obesity in rats - Mozes, S; Bujnáková, D; Sefcíková, Z; Kmet, V (Folia microbiologica, 2008)
The relationship was evaluated between early nutritional experiences, the intestinal microflora and the small intestinal functions in the mechanism of predisposition to obesity development. Male Sprague-Dawley rats were used in which the quantity of nutrition was manipulated from birth to weaning (day 30) by adjusting the number of pups in the nest to 4 small litters (SL) and 10 normal litters (NL) and fed a standard diet from days 30 to 40 of age. After 40 d, the postnatally overfed SL pups became heavier, displayed significantly enhanced adiposity, body mass gain and food intake as well as a significantly higher jejunal alkaline phosphatase and maltase activity than in rats nursed in NL nests. The effect of different early nutrition was also accompanied by the appearance of significantly decreased Bacteroides and significantly increased enterococci and lactobacilli of obese rats than in lean NL rats. The amounts of Bacteroides were negatively correlated with fat pad mass, body mass, body-mass gain and food intake whereas enterococci and lactobacilli were correlated positively with the same parameters. Our results demonstrate that postnatal nutritional experience may represent a predisposing factor influencing ontogeny of small intestine function and development of intestinal microbial communities. The acquired changes and associated alterations in food digestion could be a component of regulatory mechanisms contributing to the development of obesity and its maintenance in later life.
Keywords: Bacteroides; Animals; Enterococcus; Female; Lactobacillus; energetický příjem; ženské pohlaví; Aging; Intestine, Small; Obesity; Energy Intake; kojená zvířata; nadměrná výživa; Rats, Sprague-Dawley; tělesná hmotnost; Animals, Suckling; obezita; Male; potkani Sprague-Dawley; stárnutí; krysa rodu Rattus; Body Weight; zvířata; tuková tkáň; mužské pohlaví; Rats; Overnutrition; tenké střevo; Adipose Tissue